Removal of Methylene Blue from Aqueous Solution by Activated Carbon Prepared from Pea Shells (Pisum sativum) - Ünal Geçgel; Gülce Özcan; Gizem Çağla Gürpınar (Journal of Chemistry)
An activated carbon was prepared from pea shells and used for the removal of methylene blue (MB) from aqueous solutions. The influence of various factors such as adsorbent concentration, initial dye concentration, temperature, contact time, pH, and surfactant was studied. The experimental data were analyzed by the Langmuir and Freundlich models of adsorption. The adsorption isotherm was found to follow the Langmuir model. The monolayer sorption capacity of activated carbon prepared from pea shell for MB was found to be 246.91 mg g−1 at 25 ∘C. Two simplified kinetic models including pseudo-first-order and pseudo-second-order equation were selected to follow the adsorption processes. Kinetic studies showed that the adsorption followed pseudo-second-order kinetic model. Various thermodynamic parameters such as , , and were evaluated. The results in this study indicated that activated carbon prepared from pea shell could be employed as an adsorbent for the removal of MB from aqueous solutions.